2007
DOI: 10.1007/s00068-007-6141-6
|View full text |Cite
|
Sign up to set email alerts
|

The Kashmir Earthquake Experience

Abstract: On October 8, 2005, a major earthquake measuring 7.6 on the Richter scale struck the Himalayan region of Kashmir. Around 90,000 people died in the mass disaster. The Bone and Joint Hospital in Kashmir found itself in a relatively unique situation of having to deal with the orthopedic morbidity generated by this quake. The hospital received 468 patients over a period of 10 days, out of which 463 were received over the initial 5 days. The admission for a single day peaked at 153 patients on the third day. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Although the location of person when injury occurs and the behavior has been documented as possible reasons for the nature of injury sustained (9), there is lack of substantial evidence to make these correlations with currently available data. Head, spine, and chest injuries were comparatively low, which may be attributed to poor rescue and response operations in Gujarat (4).…”
Section: Discussionmentioning
confidence: 99%
“…Although the location of person when injury occurs and the behavior has been documented as possible reasons for the nature of injury sustained (9), there is lack of substantial evidence to make these correlations with currently available data. Head, spine, and chest injuries were comparatively low, which may be attributed to poor rescue and response operations in Gujarat (4).…”
Section: Discussionmentioning
confidence: 99%
“…This uneven distribution has also been recorded with respect to specific disaster-induced injuries (Rathore et al 2008;Bhatti et al 2008). Studies have also indicated that bone fractures are the most common injuries caused by earthquakes (Peek et al 1998;Dhar et al 2007;Ganjouei et al 2008;Xie et al 2008). However, few studies have examined variations in the gender and age of the victims of earthquake-related fractures (Pan et al 2009;Tang et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…We focus on earthquake-related fractures and amputations because they are among the most common type of injuries caused by earthquakes (Sheng 1987;Dhar et al 2007;Ganjouei et al 2008;Peek et al 1998). …”
Section: Literature Reviewmentioning
confidence: 99%
“…In Bam, published reports indicate a range from 0.4%–2.9%7 24 for some hospitals, but rates as high as 10.8%8 were indicated for patients treated in tertiary hospitals. Reports from the Kashmiri earthquake reveal rates of 0.6%–3.6%25 26 recorded in some hospitals. The amputation rate in China does not appear to have been unduly high.…”
Section: Observationsmentioning
confidence: 99%